2005
DOI: 10.1104/pp.105.063628
|View full text |Cite
|
Sign up to set email alerts
|

Light Enables a Very High Efficiency of Carbon Storage in Developing Embryos of Rapeseed

Abstract: The conversion of photosynthate to seed storage reserves is crucial to plant fitness and agricultural production, yet quantitative information about the efficiency of this process is lacking. To measure metabolic efficiency in developing seeds, rapeseed (Brassica napus) embryos were cultured in media in which all carbon sources were [U-14 C]-labeled and their conversion into CO 2 , oil, protein, and other biomass was determined. The conversion efficiency of the supplied carbon into seed storage reserves was ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(190 citation statements)
references
References 38 publications
6
183
1
Order By: Relevance
“…One further possible limitation of the in vitro system is related to the role of potential oxygen limitation during seed development. While there are no indications that in vitro-grown embryos of oilseed rape lack oxygen (Goffman et al, 2005), contrasting data have been reported for in planta developing embryos (Vigeolas et al, 2003). Under relatively low ambient light levels, reduced oxygen tension can have a strong impact on the energy state in developing oilseed rape seeds, change metabolic fluxes, and impact oil content.…”
Section: Relevance Of In Vitro Results For In Planta Seed Characterismentioning
confidence: 87%
See 2 more Smart Citations
“…One further possible limitation of the in vitro system is related to the role of potential oxygen limitation during seed development. While there are no indications that in vitro-grown embryos of oilseed rape lack oxygen (Goffman et al, 2005), contrasting data have been reported for in planta developing embryos (Vigeolas et al, 2003). Under relatively low ambient light levels, reduced oxygen tension can have a strong impact on the energy state in developing oilseed rape seeds, change metabolic fluxes, and impact oil content.…”
Section: Relevance Of In Vitro Results For In Planta Seed Characterismentioning
confidence: 87%
“…Yet, we deem the choice of our experimental system to be useful for several reasons. In multiple 13 C-based MFA studies, our in vitro embryo culture system has proven to allow well-resolved measurements of flux distribution in central metabolism (Schwender and Ohlrogge, 2002;Schwender et al, 2003Schwender et al, , 2004Schwender et al, , 2006Goffman et al, 2005;Junker et al, 2007), which is currently not achievable with a similar experimental system in planta. One further possible limitation of the in vitro system is related to the role of potential oxygen limitation during seed development.…”
Section: Relevance Of In Vitro Results For In Planta Seed Characterismentioning
confidence: 99%
See 1 more Smart Citation
“…stimulation of fatty acid synthesis in green seeds (Goffman et al, 2005). Distinct differences between the two isoforms in Arabidopsis were also discovered.…”
Section: Arabidopsis Pk P Activity Is Determined By Two B-subunitsmentioning
confidence: 94%
“…A strict light dependence of FA synthesis in leaf chloroplasts has been known for years (16), but the relevance to TAG accumulation in oilseeds was revealed only recently at the metabolic level. Even low levels of light penetrating to developing embryos provide sufficient reductant and ATP to power FA biosynthesis (17). Moreover, the activity of ribulose-bisphosphate carboxylase/oxygenase (Rubisco) in developing seeds functions not for net photosynthetic carbon fixation but rather to recycle CO 2 released by PDH and other decarboxylation reactions.…”
Section: Regulation Of Fatty Acid Supply By Plastidsmentioning
confidence: 99%